Public Perception of Halal Certification and Its Relationship with Ethical Standards in the Meat Industry - Musthafa Syukur (JURNAL ISLAM NUSANTARA, 2025)
Halal certification at slaughterhouses (RPH) plays a strategic role in ensuring the halal status of meat products and building trust among Muslim consumers. However, in Probolinggo Regency, there is still a gap between halal certification standards and their implementation in practice. This study aims to analyze public perceptions of halal certification at slaughterhouses and its relationship to consumer trust and ethical standards in the meat industry. This study used a qualitative approach with a descriptive-analytical design. Data collection was conducted through in-depth interviews, field observations, and documentation involving slaughterhouse managers, slaughterers, religious leaders, community leaders, consumers, and economic observers. Data analysis was conducted using thematic analysis with triangulation techniques to maintain data validity. The results show that positive public perceptions of halal certification include halal assurance, increased consumer trust, global competitiveness, and support for local economic growth. However, negative perceptions also emerged related to high operational costs, weak oversight, the potential for commercialization of halal certification, and low confidence in the consistency of the slaughtering process. This research contributes to enriching halal studies in the upstream food supply chain sector, particularly slaughterhouses, and provides policy recommendations to strengthen halal certification governance and supervision at the local level.